Analysis of the Effectiveness of Divorce Procedures for Government Employees with Employment Agreements in Parepare City: Siyasah Idariyah's Perspective - A.Nurgasmin A.Nurgasmin; Hasanudin Hasim; Dirga Achmad; Syafaat Anugrah Pradana (Jurnal El-Thawalib, 2026)
This study is motivated by the lack of clarity in administrative regulations regarding divorce procedures for Government Employees with Work Agreements (PPPK), as existing regulations are more focused on Civil Servants (PNS), resulting in normative and practical ambiguities. This study aims to analyze the effectiveness of divorce procedures for PPPK in Parepare City by assessing the conformity between regulations and administrative practices implemented by the regional Personel and Human Resource Development Agency (BKPSDMD). This research is a qualitative study with a normative-empirical approach. Data were obtained from primary sources through interviews and observations, as well as secondary sources in the form of laws and regulations and related documents. Data collection techniques were carried out through observation, interviews, and documentation, then analyzed qualitatively. The results show that the divorce procedures for PPPK have been implemented through administrative mechanisms with the role of BKPSDMD as the institution providing recommendations for divorce permits. The process generally takes about one month, although there are still obstacles in the form of administrative completeness and mediation processes. Thus, the effectiveness of PPPK divorce procedures is not only determined by administrative aspects, but also by legal certainty and the value of public benefit from the perspective of siyasah idariyah.